The The Effect of Teacher-Student Reciprocal Relationships on Academic Performance in Bangladeshi Primary Schools (Teacher’s World: Journal of Education and Research, 2024)
The purpose of this study was to investigate the impact of teacher-student interactions on academic success in Bangladeshi primary schools. The study employed a mixed-methods methodology and gathered data from 320 primary students and 64 instructors/teachers across sixteen elementary schools. The data collection involved the administration of survey questionnaires for both teachers and students, and focused group interviews of students and conducting semi-structured interviews with teachers. The results revealed a strong association between positive teacher-student connections and enhanced academic performance, improved student behaviour, and increased motivation. Students who reported having positive relationships with their instructors exhibited higher levels of academic success compared to those who reported negative or neutral relationships. Moreover, instructors who fostered excellent rapport with their students demonstrated higher levels of engagement and motivation, leading to improved academic achievements among their students. These findings carry significant implications for education policy and practice, emphasizing the importance of investing in teacher training and providing support to develop positive relationships with students in Bangladeshi primary schools. By prioritizing the cultivation of teacher-student bonds, educational stakeholders can potentially yield substantial improvements in student academic achievement and overall educational outcomes.Teacher’s World: Journal of Education and Res arch, 50(1): 43-60